If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -12(x) = -268 Solving 4 + -12x = -268 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -12x = -268 + -4 Combine like terms: 4 + -4 = 0 0 + -12x = -268 + -4 -12x = -268 + -4 Combine like terms: -268 + -4 = -272 -12x = -272 Divide each side by '-12'. x = 22.66666667 Simplifying x = 22.66666667
| 2x+-9(0)=9 | | 9(12/7)+7= | | .55=log(x) | | 3x-6x+6=x-5+11 | | -4m-7(6m-4)= | | (7x-4)/5=0 | | 2(12/7)-5= | | -5y^2+8y-3=0 | | 16z+5z=-3 | | 10+11(x)=87 | | 3k^2-9k+5=0 | | (w/5)=20 | | 7z-(2z-8)=-2 | | (X/-2)=(-9) | | (2x-5)=(9x+7) | | 6(1-1x)=11x-2(1x+2) | | 3v^2-8v-5=0 | | (x+1)(x+1)=(x+1)(x+1) | | -3=x/3 | | 7-3x=173 | | (6x-4)-8=12 | | -3=-4+5a-4a | | 7t^2-5t-6=0 | | 16x+3=9x+73 | | -5*a+(-5*b)=5 | | -5/8x=-60 | | ((m^(1/5))/((m^(4/5))(m^-(4)))=m^(a/b) | | 8d^2+6d+1=0 | | 5(.5-3)+3(.5+3)=2(.5)-3 | | 8u^2-9u-3=0 | | 3x^3+33x^2+90x= | | 2m^2+4m+2=0 |